Microbiological, epidemiological and clinical correlates of vaginal colonisation by Mobiluncus species. Issue 1 (February 1991) - Hillier, S L; Critchlow, C W; Stevens, C E; Roberts, M C; Wolner-Hanssen, P; Eschenbach, D A; Holmes, K K
Abstract : The microbiological and epidemiological correlates of vaginal colonisation by Mobiluncus species were examined among randomly selected women attending a sexually transmitted disease (STD) clinic. Women positive for Trichomonas vaginalis were excluded. Mobiluncus spp. were detected by Gram stained vaginal smear in 21% of 633 STD clinic patients, including 53% of those with and 4% of those without bacterial vaginosis (BV), as diagnosed by clinical criteria. Gardnerella vaginalis and Mycoplasma hominis detected by vaginal culture and Mobiluncus detected by vaginal Gram stain were each independently associated with BV after adjusting by logistic regression for the presence of sexually transmitted disease pathogens, gravidity, parity and number of lifetime sexual partners (p less than 0.001 for each organism). Bacterial vaginosis was negatively correlated with isolation of lactobacilli, yeast and herpes simplex virus. After adjusting for presence or absence of BV, women with Mobiluncus were more likely to harbour G vaginalis (odds ratio 5.6, 95% confidence interval 1.6-19.5), M hominis (OR 3.7, 95% CI 2.0-7.0) and Neisseria gonorrhoeae (OR 2.9, 95% CI 1.4-6.0) and less likely to harbour vaginal yeast (OR 0.4, 95% CI 0.2-1.0); were more likely to be black (OR 2.7, 95% CI 1.5-4.6), and to have been pregnant (OR 1.8, 95% CI 1.1-3.1); but after the adjustment for BV, vaginal colonisation by Mobiluncus was not associated with symptoms of odour, abdominal pain, menstrual irregularities, or with adnexal tenderness. In summary, Mobiluncus, Gardnerella vaginalis and Mycoplasma hominis were independently associated with a clinical diagnosis of bacterial vaginosis, and Mobiluncus was further associated with the presence of BV-associated microorganisms (M hominis and G vaginalis), N gonorrhoeae, black race, and gravidity.